Support of talents in Mathematics in the lower classes of primary school - Szelczi, Ivett; Bencéné Fekete, Andrea (Acta Scientiarum Socialium, 2014)
Support of talents in Mathematics in the lower classes of primary school The aim of this study is to raise attention to how important task of the school and the pedagogues it is to recognize the hidden talents of children; and to improve these talents in all possible ways even in this young age. In the case of Mathematics the tools of improvement are crucial. Pedagogues need methods, which make it easier for children to learn this subject. The method most preferred by the students is a game, which is enjoyable and developmental at the same time. In this paper the LÜK developmental tool will be introduced together with some helpful ways of application in the education.
Keywords: mathematics education; talent; primary school